Ecological Status and Environmental Protective Role of Avicennia officinalis in the Vulnerable Coastal Regions of Bangladesh: An overview - Rabiul Alam, Md.; Hossain, Mahmood; Masudur Rahman, Md.; Biswas, Tanay; Nasrin, Shamima; Lulu Rayhan Khushi, M. S. T. (Indian Forester, 2017)
Bangladesh is a sub-tropical deltaic country situated at the mouth of funnel shaped Bay of Bengal. The coastal regions of this country is extremely vulnerable to frequently occurring natural disasters like tropical cyclones, tidal surges,wave energy, land erosion, and salt intrusion. Avicennia officinalisÂ is a pioneer mangrove tree specie swhich plays significant ecological role in maintaining sustainable vegetation both in the Sundarbans and coastal plantations in Bangladesh, thereby protecting the coastal people from natural calamities. New land accreted at the rate of 35km2 /year in the coastal regions for the last few decades. So, A. officinalis remains one of the principal species for coastal afforestation, thereby playing its protective role in perpetuity. Salinity in the coastal regions of Bangladesh increased as a consequence of climate change and reduced freshwater flow from the upstream. A. officinalis emerged as an important mangrove species for coastal afforestation because of its tolerance to increased salinity. The species played significant role in coastal land stabilization. It also created employment opportunities for the local people in the coastal afforestation programme, thereby providing socio-economic as well as environmental protection to the people inhabiting the coastal regions of Bangladesh.